2002
DOI: 10.1080/00036840110094446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the magnitude and the stakes of peer effects analysing science and math achievement across OECD

Abstract: What follows is an exercise aimed at estimating peer effects' impact on science and math test scores of secondary school students surveyed in 1995 by the International Education Agency across OECD countries. It is also to discuss their importance for educational policy. particularly regarding the highly sensitive issue of ability-grouping. Using this unique international database. we assess the magnitude of the peer effect relative to more traditional inputs. Referring the education policy stakes, we control f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
1
17
0
6
Order By: Relevance
“…Some of these studies show that peer effects are statistically and economically significant in a variety of educational contexts and that students tend to perform better if the quality of their peer group is higher (Ding and Lehrer, 2006;Zimmerman 2003;Vandenberghe, 2002;Hoxby, 2000;Sacerdote, 2001;Zimmer and Toma, 2000). Moreover, a number of these studies show that peer effects are often non-linear, implying that students of middle abilities are particularly affected by the negative influence of weak students (Sacerdote, 2001;Zimmerman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies show that peer effects are statistically and economically significant in a variety of educational contexts and that students tend to perform better if the quality of their peer group is higher (Ding and Lehrer, 2006;Zimmerman 2003;Vandenberghe, 2002;Hoxby, 2000;Sacerdote, 2001;Zimmer and Toma, 2000). Moreover, a number of these studies show that peer effects are often non-linear, implying that students of middle abilities are particularly affected by the negative influence of weak students (Sacerdote, 2001;Zimmerman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of research has been conducted on the effects of peers on a range of student outcomes including criminal behavior (Ludwig, Duncan, & Hirschfield, 2001), substance use (Gaviria & Raphael, 2001) and body weight (Costa-Font & Gil, 2003). Peer-effects have gained much attention as moderating variables in predicting academic achievement of students in poverty (Hanushek, Kain, Markman, & Rivkin, 2003;Kang, 2007;Malecki & Demaray, 2006;Vandenberghe, 2002). However, there is little research to guide school districts in capitalizing on the potential effects of peer socioeconomic diversity on students of low SES, if any such effects exist.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Studies of international scope, such as those by Kang (2007) and Vandenberghe (2002), have shown peer-effects to be significant moderating variables in predicting academic achievement across developed nations. In 2004, Guryan compared many school districts across the United States using the black exposure index and the dissimilarity index and found that integration reduced drop-out rates of Black students and did not significantly affect White student graduation rates.…”
Section: Rationale For the Studymentioning
confidence: 99%
See 2 more Smart Citations